Characteristics of the nanostructures in thermal sprayed hydroxyapatite coatings and their influence on coating properties - Li, H. (2012)
There are generally two methods for depositing nanostructured coatings, retaining the nanostructures from starting feedstock and forming novel nanostructures through quenching. The present study utilized spray-dried nanostructured hydroxyapatite (nSD-HA) feedstock for coating/splat deposition. The nanostructures were characterized by transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM). Results revealed that the rod-shaped nano-grains in the starting HA particles (< 500 nm in length and 40–70 nm in diameter) encountered two major experiences: enlargement due to unmelt state and reorganization due to melting–solidification. The molten part of the particles results in formation of spherical nanosized particles with grain sizes of 30–110 nm. TEM observation of the HA splats demonstrates consistent nanostructures. The unmelted part of individual nSD-HA particles showed significantly enlarged grains along radial direction (< 550 nm in length and < 400 nm in diameter). In addition, individual hexagonal grains were observed in the HVOF coating made from 30 ± 10 μm powder. The grains have the size of < 250 nm in height and < 50 nm in side length and are perpendicular to the coating/substrate interface. The nanostructures within the coatings contribute to an increased Young's modulus with up to 60.11 GPa, however, they showed detrimental effect on adhesion of the coatings. In vitro cell culturing revealed marked attachment and proliferation of the osteoblast cells on the nanostructured coatings. However, the results suggest that the nanostructures possess less importance than the phases (preferably high content of crystalline HA) on enhancing the cell proliferation.